Low Oil Prices : Long-Term Economic Effects for the EU and Other Global Regions Based on the Computable General Equilibrium PLACE Model - Boratynski, Jakub; Kasek, Leszek (World Bank, Washington, DC, 2015)
Oil prices on global markets have plunged from United States (U.S.) $115 per barrel in mid-June of 2014 to U.S. $48 at end-January 2015, while other fuel prices have continued the slow downward trend of recent years. The rapid decline in oil prices by about 60 percent was accompanied by U.S. dollar appreciation against the major global currencies (except the Swiss franc), partly offsetting the oil price decline measured in currencies other than the dollar. The impact assessment of the oil price shock was conducted using a multi-county, multi-sector computable general equilibrium (CGE) model, PLACE, maintained by the Center for Climate Policy Analysis (CCPA). The effects of a permanent 60 percent oil price shock are assessed against a baseline scenario through 2020 based on the International Energy Agency (IEA) 2012 world energy outlook assuming a high oil price scenario of U.S. $118 in 2015 and U.S. $128 in 2020 (both in 2010 constant prices) and correlated price changes of coal (by 50 percent), and natural gas (by 30 percent). Model simulations show that, first, oil exporters will suffer substantial double-digit welfare losses through 2020 due to significant deterioration in their terms of trade. Second, the European Union (EU), as a large oil importer, will benefit significantly from lower oil prices, with the new member states being relatively better off, as a consequence of their relatively high energy intensity. Third, if the assumed permanent oil price shock occurs at half the level of the headline 60 percent scenario (proxying for U.S. dollar appreciation or reflecting a rebound in oil prices from their early 2015 levels through 2020), welfare effects will be smaller and less than proportional for most countries. Finally, in the EU, the existing emissions cap constrain the use of cheaper fossil fuels and limits the welfare increase by about 0.5 percentage points. The interpretation of results from the CGE model has been supported by regression, attributing the diversity of the simulated welfare effects by region to certain characteristics of regional economies, such as refined oil products-to- gross domestic product (GDP) and net exports of crude oil-to-GDP ratios.